Electrically tunable organic–inorganic hybrid polaritons with monolayer WS2 - Lucas C. Flatten; David M. Coles; Zhengyu He; David G. Lidzey; Robert A. Taylor; Jamie H. Warner; Jason M. Smith (Nature Communications, 2017)
Hybrid polariton states originating from the strong coupling of photonic and excitonic states hold promise for control of nonlinear light behaviour. Here, the authors fabricate a microcavity containing organic dye and WS2, featuring hybrid polaritons arising from both Frenkel and Wannier-Mott excitons.